2004
DOI: 10.1080/14767050310001650789
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the duration of the second stage of labor on fetal pH levels and oxidative status in uncomplicated pregnancies

Abstract: The duration of the second stage of labor up to 3 h does not influence lipid peroxidation in the fetoplacental circulation in uncomplicated pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Some reported that a prolonged second stage was an independent predictor of adverse neonatal outcomes such as acidemia, [4][5][6] while others found it to be no serious disadvantage to the fetus. [7][8][9] In our earlier small-scale study, a second stage of labor duration of < 3 hours did not influence fetal umbilical cord acid-base status, lactate status, or oxidative status in uncomplicated nulliparous women. 9) Although second stage of labor duration has been reported to be shorter in multiparous women than in nulliparous women, 10) how this impacts obstetric outcomes has not been clarified.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…Some reported that a prolonged second stage was an independent predictor of adverse neonatal outcomes such as acidemia, [4][5][6] while others found it to be no serious disadvantage to the fetus. [7][8][9] In our earlier small-scale study, a second stage of labor duration of < 3 hours did not influence fetal umbilical cord acid-base status, lactate status, or oxidative status in uncomplicated nulliparous women. 9) Although second stage of labor duration has been reported to be shorter in multiparous women than in nulliparous women, 10) how this impacts obstetric outcomes has not been clarified.…”
Section: Introductionmentioning
confidence: 66%
“…[7][8][9] In our earlier small-scale study, a second stage of labor duration of < 3 hours did not influence fetal umbilical cord acid-base status, lactate status, or oxidative status in uncomplicated nulliparous women. 9) Although second stage of labor duration has been reported to be shorter in multiparous women than in nulliparous women, 10) how this impacts obstetric outcomes has not been clarified. Against this backdrop, we examined the relationship between second stage of labor duration and lactate levels in umbilical arterial blood as a reflection of fetal acidosis in uncomplicated multiparous women.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Neonatal umbilical artery blood gas analysis (UABGA) combined with the Apgar score is currently an effective indicator for the diagnosis of fetal distress, neonatal metabolic acidosis, neonatal brain injury, and adverse neonatal outcomes. The pH, base excess (BE), and lactate parameters in UABGA are the most visual indicators of metabolic acidosis in newborns ( 5 - 7 ).…”
Section: Introductionmentioning
confidence: 99%